1998
DOI: 10.1088/0953-8984/10/4/014
|View full text |Cite
|
Sign up to set email alerts
|

Colour centres induced in LiF by low-energy electrons

Abstract: A detailed study has been carried out on the optical properties of intrinsic colour centres, created in LiF crystals under irradiation with low-penetration 3 keV electrons. The kinetics of the production of F and M centres, determined from optical absorption measurements, exhibits a typical three-stage structure and an evident saturation at high doses. The quantitative evaluation of the kinetic parameters is in excellent agreement with the predictions of the most comprehensive theoretical model. A comparison o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The volume densities of primary and aggregate CCs in LiF are very high, close to saturation values [13], and show the same behavior vs. the X-ray dose. The mean energies necessary to create the centers are 1-2 keV/center for F defects, a value already found for irradiation by low-energy electron [13], and 15 keV/center for F 2 and F 3 + aggregate defects.…”
Section: Experimental Details and Resultssupporting
confidence: 54%
“…The volume densities of primary and aggregate CCs in LiF are very high, close to saturation values [13], and show the same behavior vs. the X-ray dose. The mean energies necessary to create the centers are 1-2 keV/center for F defects, a value already found for irradiation by low-energy electron [13], and 15 keV/center for F 2 and F 3 + aggregate defects.…”
Section: Experimental Details and Resultssupporting
confidence: 54%
“…Although previous experiments done at Battelle/PNNL have shown that bulk LiF can show an unsaturated, linear fluorescence in a dose range of eight orders of magnitude when irradiated with 1.25 MeV 60 Co gamma rays, Baldacchini 31 has recently shown that while this would be expected due to the depth uniformity of the CCs created by the uniform absorption, LiF when irradiated with low energy ͑3 keV͒ electrons does show an approximate saturation level of approximately 0.3 C/cm 2 . This corresponds to an F 2 center density of 7ϫ10 20 /cm 3 .…”
Section: Results Of Pattern Encoding-decoding and Discussionmentioning
confidence: 96%
“…Others have reported a green transition at 540 nm attributed to the F 3 ϩ center which was not seen here at the laser pumping powers used. 31 The first fluorescent images in LiF for the masked ''dot'' encoding were achieved with the broad area 5 kV electron exposure. The dose used was 1.25ϫ10 3 C/cm 2 or 7.8 ϫ10 15 electrons/cm 2 .…”
Section: Results Of Pattern Encoding-decoding and Discussionmentioning
confidence: 99%
“…Extrapolation of the values of f d (D) to the ultra-low electron energies required by MTST of course introduces a degree of uncertainty in the results which is difficult to evaluate. Unfortunately the option of ultra-low energy electron irradiation [33] is also problematic due to the likelihood of dead layers/skin effects in the shallow penetration depths of such low energy electrons. Because of these difficulties a later study was carried out in LiF:MCP which does not exhibit energy-dependent-supralinearity in the dose response so that matching of the electron spectra is unnecessary [30].…”
Section: Previous Applications Of Tst To Hcp Induced Tl In Lif Materialsmentioning
confidence: 99%